Revealing the Influences of Solvent Boiling Point and Alkyl Chains on the Adlayer Crystallinity of Furan-Diketopyrrolopyrrole-Thienylene Copolymer at Molecular Level - Li, Jin-Kuo (Langmuir : the ACS journal of surfaces and colloids, 2020)
Crystallinity of the polymer poly(3,6-difuran-2-yl-2,5-di(2-octyldodecyl)-pyrrolo[3,4-c]pyrrole-1,4-dione-altthieylenevinylene) (PDVF) adlayers casted from low-boiling-point (L-bp), medium-bp (M-bp), and high-bp (H-bp) solvents was investigated through scanning tunneling microscopy (STM) and analyzed by the assistance of Hansen solubility parameter (HSP) theory and molecular dynamics (MD) simulations. Crystallinity of the PDVF adlayers increases evidently from the L- to H-bp solvents. Also, the solvent with an alkyl chain such as ethylbenzene (EB) facilitates in improving the crystallinity than the one without an alkyl chain such as chlorobenzene (CB) if the solvent bp is present in the same group. The HSP space discloses that EB is a marginal solvent for PDVF in contrast to CB. Quasi-isolate PDVF in the EB solution revealed by MD simulations facilitates the formation of crystallized domains through surface assembling mechanism. However, in CB, interconnected PDVF molecules through intermolecular overlapping tend to generate amorphous structures through direct deposition of the preformed structures in solution